Amylose crystal seeds: Preparation and their effect on starch retrogradation. (August 2020) - Zhu, Bihua; Zhan, Jinling; Chen, Long; Tian, Yaoqi
Abstract: The relationship between the short-term retrogradation dominated by amylose and the long-term retrogradation dominated by amylopectin still lacks specific experimental confirmation. In order to explore this relationship, four types of amylose crystal seeds (ACS) were prepared and added to native rice starch to intervene the long-term retrogradation. The average particle size of ACS was 200–450 nm. The maximum relative crystallinity of retrograded starch increased from 13.64% to 17.88% under the intervention of ACS. The ratio of absorbance at 1047 to 1022 cm −1 of retrograded starch increased from 0.670 to the maximum 0.887. The retrogradation rate constant increased significantly from 0.024 up to 0.051 d −1 . The long-range order, short-range order, and retrogradation rate of retrograded starch all increased significantly, which indicated that the intervention of ACS promoted the long-term retrogradation of starch. These findings provided data support for the analysis of correlation between different stages of starch retrogradation. Graphical abstract: Image 10560 Highlights: Amylose crystal seeds (ACS) increase the retrogradation rate of starch. ACS increase the long-term retrogradation dominated by amylopectin. ACS loosen the crystal cell but increase the volume of retrograded starch.